2016
DOI: 10.1590/1806-9282.62.02.184
|View full text |Cite
|
Sign up to set email alerts
|

Local management with methotrexate of cesarean scar ectopic pregnancy with live embryo guided by transvaginal ultrasound: A case report

Abstract: Cesarean scar ectopic pregnancy is a rare type of ectopic pregnancy with high morbidity and mortality. Use of conservative conducts, including medical management with methotrexate, has avoided mutilating surgeries such as hysterectomy and spared the fertility of women. We report the case of a 30-year old patient with a cesarean scar ectopic pregnancy, with a live embryo, who was treated locally with transvaginal ultrasound-guided injection of methotrexate, complemented with various doses of systemic methotrexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Based on the extracted data of the included studies [1,25,[37][38][39][40][41], the diagnosis of scar ectopic pregnancy was confirmed using various diagnostic methods, such as a transvaginal ultrasound, MRI, and transvaginal ultrasound-guided puncture. The patients presented with symptoms such as abdominal pain, vaginal bleeding, and spotting.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the extracted data of the included studies [1,25,[37][38][39][40][41], the diagnosis of scar ectopic pregnancy was confirmed using various diagnostic methods, such as a transvaginal ultrasound, MRI, and transvaginal ultrasound-guided puncture. The patients presented with symptoms such as abdominal pain, vaginal bleeding, and spotting.…”
Section: Resultsmentioning
confidence: 99%
“…In cesarean scar pregnancy when the embryo/fetus has heartbeat, local methotrexate (1 mg/kg) treatment guided by transvaginal ultrasound should be the first option [23] (Figures 8 and 9). The current scientific evidences demonstrate that local treatment with MTX brings best results.…”
Section: Cesarean Scar Pregnancymentioning
confidence: 99%